2018
DOI: 10.1016/j.actbio.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Improving functional re-endothelialization of acellular liver scaffold using REDV cell-binding domain

Abstract: There is a critical need for novel organ replacement therapies as the grafts for transplantation fall short of demand. Recent advances in tissue engineering, through the use of decellularized scaffolds, have opened the possibility that engineered grafts could be used as substitutes for donor livers. However, successful implantation has been challenged by the inability to create a functional vasculature. Our research study reports a new strategy to increase efficiency of endothelialization by increasing the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 61 publications
0
55
1
Order By: Relevance
“…Nonetheless, inconsistent results have been reported for the efficacy of REDV functionalization. Some studies report improved adhesion of endothelial cells but do not compare to RGD or other peptides for functionalization, or adhesion of other mammalian cell types., or show unexpected failed refunctionalization for other cell‐types with RGD . Other studies also unexpectedly show reduced endothelial cell adhesion on REDV functionalized surfaces compared to RGD …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, inconsistent results have been reported for the efficacy of REDV functionalization. Some studies report improved adhesion of endothelial cells but do not compare to RGD or other peptides for functionalization, or adhesion of other mammalian cell types., or show unexpected failed refunctionalization for other cell‐types with RGD . Other studies also unexpectedly show reduced endothelial cell adhesion on REDV functionalized surfaces compared to RGD …”
Section: Resultsmentioning
confidence: 99%
“…Besides peptides such as RGD, which induce cell adhesion in general, peptide sequences have been discovered for which specific cell types have an increased affinity over other cell types, due to increased expression of the binding motif on these cells . The REDV peptide, for which endothelial cell‐specificity has been reported, attributed to binding to integrin α4β1, has been extensively applied to enhance endothelialization of biomaterials . In another approach, a peptide derived from stromal cell derived factor‐1α (SDF1α), a chemoattractant of lymphocytes, monocytes, and progenitors cells, has been applied for improved in situ cellularization…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that spontaneous endothelialization failed to take place in humans following implantation of small‐diameter vascular grafts made of synthetic polymers even after long‐term implantation. In order to improve both biocompatibility and EC adhesion, many peptide sequences, such as RGD and REDV, have been grafted onto artificial vascular grafts. While peptides have been used for vascular tissue engineering for a decade, they have not been extensively studied in whole organ bioengineering.…”
Section: Discussionmentioning
confidence: 99%
“…The decellularization process for the production of an acellular organ scaffold has been under development for many years, and the results have been quite remarkable . However, the recellularization process has proven to be very challenging, and the major obstacle to successful organ bioengineering is re‐endothelialization . Improving the re‐endothelialization efficiency would be a dramatic breakthrough for the regeneration of transplantable organs.…”
Section: Introductionmentioning
confidence: 99%
“…et al constructed a vascular graft based on electrospun PCL matrix, on which organoseleniumimmobilized polyethyleneimine (SePEI) for in situ nitric oxide (NO) generation and hyaluronic acid (HA) grafted with poly (ethylene glycol) (PEG) modified Tyr-Ile-Gly-Ser-Arg (YIGSR) for antifouling and ECs adhesion were deposited through electrostatic layer-by-layer assembly. Since α 4 β 1 integrin mainly expressed on ECs and EPCs, REDV possesses the capability of specifically enhancing ECs/EPCs adhesion(Devalliere, Chen, Dooley, Yarmush, & Uygun, 2018;Wei et al, 2011).Tetsuji Yamaoka et al modified REDV peptides on their decellularized graft, which was the first TEVG study using a long-bypass graft in an animal model. The outmost layer of YIGSR peptides exhibited the facilitation of more rapid and organized ECs adhesion compared to PCLand non-modified grafts(Tang et al, 2018).…”
mentioning
confidence: 99%